Raimundo Analisis Strategi Konten Digital Marketing dan Copywriting pada Media Sosial - Raimundo; Julianti Kasih (Journal of Smart Technology and Engineering, 2026)
This investigation analyzes social media content strategies on the MyGRACE.id Instagram account for the period of October to November 2025. The primary issue underlying this research is the fluctuation in audience interaction and the need for a more systematic standardization of digital content production. The main objective is to design relevant digital marketing content ideas and implement effective copywriting techniques to enhance audience engagement. The methodology employed is a qualitative descriptive approach with historical performance data comparison analysis, as well as business process modeling using Business Process Modeling Notation (BPMN) to optimize the workflow between content managers and interns. This research analyzes a dataset of 97 digital content pieces published on the MyGRACE.id Instagram account during the 13 October 2025–30 November 2025 observation period. The research results indicate that high view performance was significantly achieved through synergy between short video formats (Reels), topics with strong emotional resonance such as interpersonal relationships, and the use of copywriting techniques based on the principle of clarity. The use of AI-based tools like Magic Write proved helpful in narrative efficiency, while the transition of language style from personal to inclusive ("Kita") successfully increased emotional proximity with followers. Statistical data shows performance stability with an increase in total views reaching 1,874 in November, dominated by new audiences (non-followers) through video content. The study's conclusion emphasizes that alignment between consistent visual elements and empathetic writing is the key to increasing active audience interaction. This research provides practical implications for social media managers in optimizing audience acquisition through integrated content strategies.